Land Suitability Assessment for Maize Development in Dulamayo Garden Farming of Gorontalo Regency - Nurdin Nurdin (Perkebunan dan Lahan Tropika, 2012)
The aimed of this research was to determining of upland suitability for maize commodity development and its limiting factors based on land quality. This research conducted at three month in Dulamayo garden farming of Gorontalo State University. Assessments of land suitability classes using the framework of land evaluation and parametric approach with root square land index as methods. The result of this research showed that the land suitability classes showed that land utilization type (LUT) for Local Maize of patterns A (none fertilizing) + B (national fertilizing dosage) were dominantly of moderately suitable with nutrient availability as limiting factors (S2na), while for pattern C (prescription fertilizing dosage) was very suitable but any small amount of nutrient availability as limiting factors (S1na). The LUT Composite Maize to pattern A was marginally suitable with nutrient availability as limiting factors (S3na), pattern B same as LUT Local Maize limiting factors, but pattern C with very suitable classes but differences of limiting factors (S1wa). For LUT Hybrids Maize dominantly of marginally suitable with water availability as limiting factors (S3wa) to pattern A+B, but pattern C dominantly of moderately suitable with water availability as limiting factors (S2wa).  Keywords: Suitability class, parametric, upland, maize.